2016
DOI: 10.1002/eat.22631
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect costs among patients with binge‐eating disorder in the United States

Abstract: Individuals with BED reported significantly greater economic burden with respect to work productivity loss, level of healthcare resource utilization, and costs compared to non-BED respondents. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:523-532).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Over half of the providers selected recurrent use of inappropriate compensatory behaviors to prevent weight gain as a diagnostic criterion for BED, suggesting that providers confused the diagnosis of BED with bulimia nervosa and that BED was not recognized as a discrete eating disorder. These findings are especially important considering that prompt detection of eating disorders and referral for tailored treatment may help to prevent medical and psychosocial complications associated with BED (Johnson, Spitzer, & Williams, ; Ling et al., ; Thornton et al., ; Ulfvebrand et al., ). For example, overweight and obesity are common among patients with BED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over half of the providers selected recurrent use of inappropriate compensatory behaviors to prevent weight gain as a diagnostic criterion for BED, suggesting that providers confused the diagnosis of BED with bulimia nervosa and that BED was not recognized as a discrete eating disorder. These findings are especially important considering that prompt detection of eating disorders and referral for tailored treatment may help to prevent medical and psychosocial complications associated with BED (Johnson, Spitzer, & Williams, ; Ling et al., ; Thornton et al., ; Ulfvebrand et al., ). For example, overweight and obesity are common among patients with BED.…”
Section: Discussionmentioning
confidence: 99%
“…BED is reported by 9% to 20% of patients seeking weight loss (Hartmann et al., ; Striegel‐Moore & Franko, ). The disorder is associated with significant health problems, including medical complications such as type 2 diabetes and metabolic syndrome, psychosocial and functional impairment, and healthcare resource utilization and cost (Ágh et al., ; Ling, Rascati, & Pawaskar, ; Thornton et al., ; Ulfvebrand, Birgegård, Norring, Högdahl, & von Hausswolff‐Juhlin, ; Watson et al., ). Over half of patients with BED experience impairments in role functioning (Hudson et al., ), and compared to individuals without BED, those with BED have worse physical and mental health‐related quality of life (Ágh et al., ).…”
mentioning
confidence: 99%
“…This is possibly because the target populations were adolescents who were not yet in the workforce (Byford et al, 2007; Wang et al, 2011). Having said that, the cost-effectiveness of interventions might be underestimated given that the societal costs associated with EDs are substantial (Ling et al, 2016, Stuhldreher et al, 2012, 2015). Another limitation is that conclusions regarding the long-term cost-effectiveness of the interventions, especially in ED treatment, cannot be made since only 4 out of 13 studies included time frames beyond two years.…”
Section: Discussionmentioning
confidence: 99%
“…In a US-based survey of working adults, respondents meeting BED diagnostic criteria had significantly higher percentages of absenteeism, presenteeism, and work productivity loss than those not meeting BED diagnostic criteria [16]. Furthermore, another US-based survey found that individuals meeting BED diagnostic criteria had higher healthcare resource utilization and costs compared with individuals not meeting BED diagnostic criteria [12]. Given the evidence indicating that individuals with BED have a higher incidence of dyslipidemia, hypertension, and type 2 diabetes [17], the costs associated with those comorbid conditions could compound the existing economic burden of BED.…”
Section: Introductionmentioning
confidence: 99%
“…Untreated or undertreated BED poses health and economic burdens [12][13][14][15][16]. In a US-based survey of working adults, respondents meeting BED diagnostic criteria had significantly higher percentages of absenteeism, presenteeism, and work productivity loss than those not meeting BED diagnostic criteria [16].…”
Section: Introductionmentioning
confidence: 99%